Black carbon and mineral dust in snow cover on the Tibetan Plateau - Zhang, Yulan; Kang, Shichang; Sprenger, Michael; Cong, Zhiyuan; Gao, Tanguang; Li, Chaoliu; Tao, Shu; Li, Xiaofei; Zhong, Xinyue; Xu, Min; Meng, Wenjun; Neupane, Bigyan; et al. (Copernicus, 2018)
Snow cover plays a key role for sustaining ecology and society in mountainous regions. Light-absorbing particulates (including black carbon, organic carbon, and mineral dust) deposited on snow can reduce surface albedo and contribute to the near-worldwide melting of snow and ice. This study focused on understanding the role of black carbon and other water-insoluble light-absorbing particulates in the snow cover of the Tibetan Plateau (TP). The results found that the black carbon, organic carbon, and dust concentrations in snow cover generally ranged from 202 to 17 468 ng g−1, 491 to 13 880 ng g−1, and 22 to 846 µg g−1, respectively, with higher concentrations in the central to northern areas of the TP. Back trajectory analysis suggested that the northern TP was influenced mainly by air masses from Central Asia with some Eurasian influence, and air masses in the central and Himalayan region originated mainly from Central and South Asia. The relative biomass-burning-sourced black carbon contributions decreased from ∼ 50 % in the southern TP to ∼ 30 % in the northern TP. The relative contribution of black carbon and dust to snow albedo reduction reached approximately 37 and 15 %, respectively. The effect of black carbon and dust reduced the snow cover duration by 3.1 ± 0.1 to 4.4 ± 0.2 days. Meanwhile, the black carbon and dust had important implications for snowmelt water loss over the TP. The findings indicate that the impacts of black carbon and mineral dust need to be properly accounted for in future regional climate projections, particularly in the high-altitude cryosphere. ISSN:1994-0416 ISSN:1994-0424